2017
DOI: 10.1177/1469540517717776
|View full text |Cite
|
Sign up to set email alerts
|

Building community, benefiting neighbors: “Buying local” by people who do not fit the mold for “ethical consumers”

Abstract: According to nearly all studies, ethical consumption is a regular practice mainly of people who are well educated and politically active in conventional ways. Buying local has also recently been portrayed as part of an “eco-habitus” associated with ecological thinking, cultural capital, and the desire for more “authentic” things. In this article, I challenge both these notions. Specifically, drawing on Holt’s model of the relationship between cultural capital and consumption, I make two arguments. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…This local purchasing behavior benefits the nation on economic, social (community), and environmental levels. Though buying local is sometimes considered to overlap with green consumerism, [34] argued that consumers with low incomes and poor educationswhich are the typical characteristics of consumers in developing countriesare motivated to buy local for social and economic benefits but not necessarily out of environment concern. [35] reported that consumers in developing countries that have a strong global culture trend strongly towards materialistic and environmental values.…”
Section: E Categorical Cognition Theorymentioning
confidence: 99%
“…This local purchasing behavior benefits the nation on economic, social (community), and environmental levels. Though buying local is sometimes considered to overlap with green consumerism, [34] argued that consumers with low incomes and poor educationswhich are the typical characteristics of consumers in developing countriesare motivated to buy local for social and economic benefits but not necessarily out of environment concern. [35] reported that consumers in developing countries that have a strong global culture trend strongly towards materialistic and environmental values.…”
Section: E Categorical Cognition Theorymentioning
confidence: 99%
“…The overview of literature data allows concluding that the scope of research into the local food is associated to a much lesser extent with the cognitive and affective component, and to a greater extent with the behavioral component of the investigated consumer attitudes (Cranfield et al, 2012;Megicks et al, 2012;Maples et al, 2013;Memery et al, 2015;Tackie et al, 2015;Schoolman, 2017). In most studies, it is not the buyers that are the subject of the study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Organic food sales in the United States rose from $21.3 billion in 2009 to $47.9 billion in 2018, while the local food market in the United States-characterized by direct-to-consumer sales, farmers' markets, farm-to-table restaurants, and farm-toschool programs-grew from about $5 billion in 2008 to an estimated $20 billion by 2020 (Organic Trade Association, 2019; Stone, 2018). Key reasons for purchasing include environmental and health concerns, food quality and food safety, and an interest in supporting local farmers and economies (Onozaka et al, 2010;Schoolman, 2017, Zepeda & Deal, 2009. So-called "locavorism" has also caught the attention of the nation's largest supermarket chains, nearly all of which have begun to increase their local food procurement; retailers like Wal-Mart, Costco, and Kroger account for the largest volume of organic food sales (Beck & Reich, 2018;Chait, 2019).…”
Section: Food Systems Trust and Transparencymentioning
confidence: 99%
“…Organic food sales in the United States rose from $21.3 billion in 2009 to $47.9 billion in 2018, while the local food market in the United States—characterized by direct-to-consumer sales, farmers’ markets, farm-to-table restaurants, and farm-to-school programs—grew from about $5 billion in 2008 to an estimated $20 billion by 2020 (Organic Trade Association, 2019; Stone, 2018). Key reasons for purchasing include environmental and health concerns, food quality and food safety, and an interest in supporting local farmers and economies (Onozaka et al, 2010; Schoolman, 2017, Zepeda & Deal, 2009).…”
Section: Food Systems Trust and Transparencymentioning
confidence: 99%